16,17-Dihydro Gibberellin A(5) Competitively Inhibits a Recombinant Arabidopsis GA 3β-Hydroxylase Encoded by the GA4 Gene - Zhou, Rong (American Society of Plant Biologists, 2004)
Ring D-modified gibberellin (GA) A(5) and A(20) derivatives are structurally similar to GA(20) and GA(9) (the precursors to growth-active GA(1) and GA(4)) and, when applied to higher plants, especially grasses, can reduce shoot growth with concomitant reductions in levels of growth-active GAs and increases in levels of their immediate 3-deoxy precursors. The recombinant Arabidopsis GA 3β-hydroxylase (AtGA3ox1) protein was used in vitro to test a number of ring D-modified GA structures as possible inhibitors of AtGA3ox1. This fusion protein was able to 3β-hydroxylate the 3-deoxy GAs, GA(9) and GA(20), to GA(4) and GA(1), respectively, and convert the 2,3-didehydro GA, GA(5), to its 2,3-epoxide, GA(6). Michaelis-Menten constant (K(m)) values of 1.25 and 10 μm, respectively, were obtained for the GA(9) and GA(20) conversions. We utilized the enzyme's ability to convert GA(20) to GA(1) in order to test the efficacy of GA(5), 16,17-dihydro GA(5) (dihydro GA(5)), and a number of other ring D-modified GAs as inhibitors of AtGA3ox activity. For the exo-isomer of dihydro GA(5), inhibition increased with the dose of dihydro GA(5), with Lineweaver-Burk plots showing that dihydro GA(5) changed only the K(m) of the enzyme reaction, not the V(max), giving a dissociation constant of the enzyme-inhibitor complex (K(i)) of 70 μm. Other ring D-modified GA derivatives showed similar inhibitory effects on GA(1) production, with 16,17-dihydro GA(20)-13-acetate being the most effective inhibitor. This behavior is consistent with dihydro GA(5), at least, functioning as a competitive substrate inhibitor of AtGA3ox1. Finally, the recombinant AtGA3ox1 fusion protein may be a useful screening tool for other effective 3β-hydroxylase inhibitors, including naturally occurring ones.